Green Food Industry in China: Spatial Pattern and Production Concentration Drivers - Sun, Chuanzhun; Huang, Diejun; Li, Hua; Chen, Cheng; Wang, Chao; Li, Minting; Wang, Zichen (Frontiers in Environmental Science, 2021)
China is the largest manufacturing country globally and currently faces severe environmental problems. China needs to identify a new mode of economic growth to contribute towards environmental protection. Developing the green industry is China’s national strategy to achieve a sustainable path and prevent further degradation of the environment. This study used China’s green food certification enterprise location data to investigate the green food industry’s spatial patterns in 2018 at the agricultural district, provincial, and city levels. Then, using the geographically weighted regression (GWR) method, we evaluated the factors impacting the green food industry’s concentration. Fourteen impact factors were selected from three aspects: socioeconomic, natural, and other factors corresponding to the regional food production potential. Our results showed the following: (1) the structure and species of green food enterprises are simple, and most enterprises are plant products upstream of the industrial chain, with low additional value. There is a large potential to increase the ratio of livestock, poultry, and fishery products; (2) the regional development of the green food industry is not uniform. The green food industry tends to concentrate along the eastern coastline and Yangtze River, and the middle-lower Yangtze Plain, Huang-Huai-Hai Plain, and North East Plain account for 76% of the total production capacity. However, northern China has the highest production ability among single enterprises;(3) regional economies, natural resource conditions, and environmental quality largely impact the concentration of the green food industry. In particular, the green food industry is concentrated in regions with high gross economic levels, highly advantageous natural conditions, and high proportion of cultivated land, except cereal planting areas. Better air quality has a positive influence on the food industry’s concentration.